Educating the masses for the middle path strategy and the political action of the Islamic base political parties post Malaysia 12th general election, 2008 - Othman, M.R. (2008)
In recent years efforts have been made to improve governance by ensuring institutional performance and policing for greater transparency to sustain liberal democracy in Bangladesh and elsewhere. Since gaining independence in 1971, The People’s Republic of Bangladesh has been driven by internal power struggles and economic chaos, while attempting to develop a democratic society. A predominately Islamic country, Bangladesh’s representative government is battling poverty and rampant corruption. Although this study appreciates what Bangladesh has achieved so far, it seeks to deviate from the general trend that romanticizes Bangladesh’s democracy and its recent connection with new governance parameters. This study attempts to identify some of the major paradoxes that Bangladesh’s democracy is faced with. All these factors will be analyzed in the context of a contemporary notion of governance and democracy in Bangladesh.